Successful pregnancy complicated by persistent pneumothorax in a patient with lymphangioleiomyomatosis (LAM) on sirolimus - Faehling, >M.; Frohnmayer, S.; Leschke, et al., M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
We report a successful pregnancy in a patient with longstanding LAMon treatment with sirolimus. During temporary discontinuation fo sirolimus in early pregnancy, lung function declined but recovered after resumption of sirolimus. Pregnancy was complicated by a persistent pneumothorax which was treated surgically postnatally. The child has had a normal development despite exposure to low dose sirolimus intermittently during early embryonal and mid-fetal life.